Advanced exit sign / Siti Fatin Nabila Samsul Bahari and Azira Ibrahim - Samsul Bahari, Siti Fatin Nabila; Ibrahim, Azira (2023)
This paper presents a new concept of an Advanced Exit Sign designed for installation in commercial buildings. It addresses the issue of occupants who may have visual impairments, providing assistance in finding a way out during emergencies. The main purpose behind the concept of the Advanced Exit Sign is to elevate safety standards by designing a revolutionary exit sign which is integrated with an alarm system, flickering light-emitting diode (LED) lights, and LED strip lights. The aim of this research is to produce technology in managing exit sign systems that can be used by all occupants of commercial buildings. The objectives are to design sign ideas for the Advanced Exit Signs, assemble a prototype, demonstrate the performance of the sign, and propose a business plan for the product. The method used in this study employs innovation framework based on design thinking. The suggested innovation idea was developed from a basic hand sketch to a three-dimensional (3D) model using the SketchUp Pro 2022 programme, enhancing the visual representation of the concept.